2001
DOI: 10.1097/00125817-200101000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological profile of children and adolescents with the 22q11.2 microdeletion

Abstract: Purpose: Patients with one of the 22q11.2 deletion syndromes provide a unique opportunity to research the interface between genetics and brain-behavior relationships. This study investigates the neuropsychological characteristics and behavioral phenotype of children with this deletion syndrome. Methods: We report updated findings from descriptive and nonparametric analyses of neuropsychological data from 80 children with the 22q11.2 deletion. Results: The subjects showed higher verbal than nonverbal IQ scores,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
228
7
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(258 citation statements)
references
References 32 publications
18
228
7
2
Order By: Relevance
“…It may be that attention deficits in 22q11DS are located in processes which place more demands on executive functions such as selectivity, inhibition or processing capacity (Posner & Peterson, 1990;Rossi, Pessoa, Desimone&Ungerleider, 2009). This would fit with previous findings of poor executive functioning in 22q11DS (e.g., Campbell et al, 2009;Woodin et al, 2001). Therefore, it cannot be concluded from these results that there were no differences in attention between the groups, rather that there were no differences in vigilance as measured by reaction time.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It may be that attention deficits in 22q11DS are located in processes which place more demands on executive functions such as selectivity, inhibition or processing capacity (Posner & Peterson, 1990;Rossi, Pessoa, Desimone&Ungerleider, 2009). This would fit with previous findings of poor executive functioning in 22q11DS (e.g., Campbell et al, 2009;Woodin et al, 2001). Therefore, it cannot be concluded from these results that there were no differences in attention between the groups, rather that there were no differences in vigilance as measured by reaction time.…”
Section: Discussionsupporting
confidence: 85%
“…Neuropsychological research over the last decade has successfully delineated a neurocognitive profile associated with 22q11DS, which indicates a range of deficits in spatial cognition (e.g., Simon, Bearden, McDonald-McGinn, &Zackai, 2005;Simon, 2008), including motor abilities (Van Aken, Caeyenberghs, Smits-Engelsman, & Swillen, 2009;Van Aken et al, 2007) and visual-spatial and perceptual processing in adults (e.g., Henry et al 2002). Impairments in sustained attention have also been widely reported (Campbell et al, 2010;Niklasson, 2006;Woodin et al, 2001) and one study reported sustained attention deficits after controlling for IQ (Lewandowski, Shashi, Berry, &Kwapil, 2007). However, the majority of studies of neurocognitive function in 22q11DS have not adequately controlled for the effects of intellectual disability, commonly reported to be in the borderline to moderate range in 22q11DS with a mean FSIQ of 70 and a prevalence of approximately 80% (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Both the 22q11.2 deletion and disorders within the autism spectrum include a broad range of behavioral patterns, and evolving definitions for ASDs have greatly increased their apparent frequency (Yergin-Allsop et al, 2003). Many researchers who have examined behavioral difficulties in individuals with the 22q11.2 deletion have utilized broadband behavior checklists (Swillen et al, 1999;Woodin et al, 2001), and none have included comprehensive evaluations of autism spectrum behaviors in particular. All of these issues have rendered determining the prevalence of ASDs among individuals with the 22q11.2 deletion quite difficult.…”
mentioning
confidence: 99%
“…Neuropsychological test results suggested that the primary deficits among children with 22q11DS were likely to include attention, executive function, [6][7][8] and motor behavior, 7 three functional domains that are linked in the brain. Performance of children with 22q11DS on tasks that tapped more specific brain pathways within these relatively broad functional regions have helped to substantiate these initial findings.…”
mentioning
confidence: 99%